Development and Quality Assessment of Mango Peel Powder Incorporated Functional Carabeef Cookies - M, M. Goswami; Sharma, B. D.; Mendiratta, S. K.; Pathak, V.; Kumar, R. R.; Talukdar, S. (Journal of Meat Science, 2017)
The present study was carried out to develop and assess the quality attributes of fiber enriched functional carabeeef cookies. The products were formulated with incorporation of mango peel powder (MPP) by replacing refined wheat flour as: Control (C) with no mango peel powder, MT1 (with 5% MPP), MT2 (with 10% MPP) and MT3 (with 15% MPP). There was a significant difference (p
Keywords: Carabeef cookies; Mango peel powder; Qual